Effect of Social Media Influencers on Purchase Intention in shopping of Electronic Goods - Nasrin Haque , Umama; Mazumder, Rabin (International Journal of Psychosocial Rehabilitation, 2020)
Social media and the internet play an important role in assisting consumers to get the particular items they are looking for. Social media influencers have emerged as a dynamic third-party endorser. Social media influencers are regularly in touch with their followers by constantly updating them about the latest information. With platforms like Facebook, Twitter, Instagram, and YouTube, social media influencers are strategically used to promote products or services to their online followers. This study is intended to explore the effectiveness of social media influencers with a focus on source credibility, source attractiveness, and meaningful transfer. The main aim of this study is to examine the effect of social media influencers on purchase intention with a focus on shopping for electronic goods. The research study is based on primary data, which is collected through questionnaires. A suitable questionnaire was used based on the objectives of the study. The items of the independent and dependent variables were measured based on a five-point Likert scale ranging from strongly disagree, disagree, neutral, and agree to strongly agree. The measurement of the relationship of the study was subjected to rigorous data processing and analysis using relevant computer software tools. Descriptive as well as inferential statistics were used. Structured Equation Modelling (SEM) was conducted on the data in order to understand a set of relationships between one or more independent variables and between one or more dependent variables. All hypotheses are found to be supportive. The mediating effect of customer attitude is also observed. Results in this study suggest that respondents who have a favorable attitude towards social media influencers will generally have the motive to purchase the influencer’s endorsed product. From a managerial implication perspective, this study offers marketers several practical opinions on selecting the particular social media influencer in order to gain a competitive advantage in the industry. Hence, marketers should select the appropriate social media influencer in order to increase the purchase intention of the consumers.